'Architects in war': wartime destruction and architectural practice during the siege of Sarajevo. Issue 6 (17th August 2020) - Pilav, Armina
Abstract : During the war in Bosnia and Herzegovina (1992–1996), standard practices of architectural investigation and design processes, such as visiting specific sites, became too dangerous. Located in a valley, Sarajevo was besieged for four years. It was subjected to constant military attacks. The destruction of the city followed two directions. At the same time that shelling was undoing the city's architecture, the control and remote occupation of public space by sniper gunmen instigated the creation of ephemeral spaces for protection and survival. The military siege rescaled the urban landscape and people's homes. In 1993, architect Zoran Doršner documented how this had also transformed the architectural programme of typical modernist dwellings into self-organised spaces. Documenting the shelling of the city and its destruction during the war, Sarajevo's architects were directly engaged with the 'city at war'. Relying on their experience of survival and their pre-war architectural practice, they created temporary methods for the architectural observation and documentation of the city under destruction. Ivan Štraus witnessed the destruction of the city from his terrace. He gathered his observations in a diary entitled 'Architects and Barbarians' (1995). In 1993, Lebbeus Woods visited Sarajevo. Taking the role of a journalist, he presented his pamphlet War and Architecture . To understand architects' practices in the wartime city, this article revisits documents that were produced during the war. These include the abovementioned diary and pamphlet, the reports on Sarajevo's destruction published in the special issue of ARH architecture magazine on 'Warchitecture' (1993), and archival photographs, sketches, and drawings. The work and role of 'architects in war' remains largely unexplored in architectural theory and history. Through the methods employed by Sarajevo's architects and citizens, this article attempts to introduce a research lexicon of architectural practices and ephemeral interventions by 'architects in war'.